2019
DOI: 10.1088/1757-899x/602/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Study on static electrification of the PFAE-mineral oil mixture

Abstract: The natural ester of tri-ester type has been implemented on a high voltage large power transformer, rated at 420 kV, since 2014. The high voltage transformer is known prone to the static electrification risk. Palm fatty acid ester (PFAE) which is a monoester oil type has also been tried on the high voltage power transformer. For a retrofilling purpose, some portion of the previously used insulating oil (it is mainly mineral oil) will remain in the transformer. It is then demanded to study the static electrific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Energies 2020, 13, x FOR PEER REVIEW 2 of 12 [12] gave a solution for the streaming current measurements using conductive materials. Consequently, the ECT of pure hydrocarbons and their mixtures [13][14][15], mineral and synthetic oils [16][17][18][19][20][21][22][23][24][25][26][27], natural and synthetic esters [28][29][30], and their mixtures with mineral oil [31,32] were examined. The research results show that the process of mineral oil electrification is very complex and depends on physicochemical properties that change due to temperature, aging processes, humidity, and electric field strength, among others.…”
Section: Methodsmentioning
confidence: 99%
“…Energies 2020, 13, x FOR PEER REVIEW 2 of 12 [12] gave a solution for the streaming current measurements using conductive materials. Consequently, the ECT of pure hydrocarbons and their mixtures [13][14][15], mineral and synthetic oils [16][17][18][19][20][21][22][23][24][25][26][27], natural and synthetic esters [28][29][30], and their mixtures with mineral oil [31,32] were examined. The research results show that the process of mineral oil electrification is very complex and depends on physicochemical properties that change due to temperature, aging processes, humidity, and electric field strength, among others.…”
Section: Methodsmentioning
confidence: 99%
“…The authors found big differences in the form of the current characteristics depending on whether the oil used was fresh or aged. Rajab et al [25] presented research on ECT results of PFAE (palm fatty acid ester) and mineral oil mixtures at various percentage ratios of PFAE. The authors showed that electrostatic charging tendency increases with the percentage ratio of PFAE to 80% but then decreases for the liquid containing only PFAE.…”
Section: Introductionmentioning
confidence: 99%
“…Similar dependencies between the parameters being studied were obtained for the mixtures of Trafo EN mineral oil with Envirotemp FR3 natural ester [37], and with Midel 1204 natural ester and Midel 7131 synthetic ester [38]. Rajab et al [42] presented the results of their studies on the electrification in mixtures of PFAE (palm fatty acid ester) with fresh and used mineral oil. The authors also observed the characteristic maximum of the electrification current, when the content of PFAE was 80%.…”
Section: Resultsmentioning
confidence: 60%